2004
DOI: 10.1118/1.1796151
|View full text |Cite
|
Sign up to set email alerts
|

Lubberts effect in columnar phosphors

Abstract: Noise transfer in granular x-ray imaging phosphor screens is not proportional to the square of the magnitude of the signal transfer when the transfer properties are considered for the entire screen thickness, unless appropriately weighted at each depth of interaction. This property, known as the Lubberts effect, has not yet been studied in columnar structured screens because of a lack of a generalized description of the depth-dependent light transport. In this paper, we investigate the signal and noise transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
69
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 35 publications
0
69
1
1
Order By: Relevance
“…Physical and scintillating properties of granular Gd 2 O 2 S:Tb and columnar CsI:Tl phosphor materials: (i) material's density, r [9], (ii) packing density,r p [14,54], (iii) intrinsic efficiency, Z c [14,15] and (iv) optical parameters s, t, r 0 , r 1 (present study). physical wide sense stationary (WSS) process that governs the transfer of signal from the input to the output [15,29].…”
Section: Tablementioning
confidence: 98%
“…Physical and scintillating properties of granular Gd 2 O 2 S:Tb and columnar CsI:Tl phosphor materials: (i) material's density, r [9], (ii) packing density,r p [14,54], (iii) intrinsic efficiency, Z c [14,15] and (iv) optical parameters s, t, r 0 , r 1 (present study). physical wide sense stationary (WSS) process that governs the transfer of signal from the input to the output [15,29].…”
Section: Tablementioning
confidence: 98%
“…We assume w ¼ 17 [27] and 3.6 eV [28] for the Gd 2 O 2 S:Tb phosphor and the Si photodiode, respectively. For the purposes of the calculations, it is assumed the optical collection efficiency is h scn ¼ 0.1 and charge collection from direct interactions is h pd ¼ 1 for both front and rear detectors.…”
Section: Cascaded-systems Analysismentioning
confidence: 99%
“…Mean free paths of absorption and scattering were taken to be 1 and cm, respectively [4]. The side surface of a phosphor screen was defined as a metal surface with a reflection coefficient of zero, which implies that the optical photon escaping through the side surface never comes back and its simulation is terminated.…”
Section: E Monte Carlo Simulationsmentioning
confidence: 99%
“…In thick phosphors, the Lubberts' effect suggests that the NPS may fall off with frequency more slowly than MTF because of depth-dependent interaction of x-rays and light collection [3]. Badano et al [4] demonstrated the Lubberts' effect in a phosphor screen by estimating the Lubberts fraction, , based on a Monte Carlo simulation. However, our own studies using a phosphor screen having a thickness similar to that of Badano showed a greater deviation from the simple MTF model than predicted by the Lubberts' effect, suggesting another mechanism is causing NPS degradation.…”
Section: Introductionmentioning
confidence: 98%